A hardware-in-the-loop simulation and test for unmanned ground vehicle on indoor environment - Khalid, Yunus; Saesar, Luhur Budi; Herawan, Tutut (Elsevier Ltd, 2012)
In this paper, we present an alternative approach for analyzing performance and monitoring of unmanned ground vehicle (UGV) through a Hardware-in-the-loop (HIL) simulation. This approach is started by defined a mathematical model of kinematic-dynamic forces apply and sensor-actuator model that integrated in UGV for simulation. A novel hardware control architecture was built to meet the HIL simulation method. Both simulation model and hardware configurations are provided by MATLAB/simulink toolboxes. To verify the HIL system, 2 small fields was built for the real test. Moreover 3D virtual model of UGV and the environment test field was developed to ease the system monitoring. Finally from the tracking system, results show that the HIL simulation method combined with the real environment produce more information of parameter that influenced during the tests given.